The reality of business process reengineering at Palestine private university and Gaza private university from the point of view of academics and administrators in both universities - Abu Aisha, Mahmoud Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the reality of business process reengineering at Palestine private university and Gaza private university from the point of view of academics and administrators in both universities, and the study applied the analytical survey descriptive method depending on primary and secondary sources of data, and the questionnaire was used as a main tool for collecting data, that questionnaire was distributed over a sample consists of (186) employees of academic and administrative employees who are working at that both universities, and the study revealed that the applying of business process reengineering by Palestine private university and Gaza private university –from point of view of the sample- got total average of (3.91 out of 5) with a large degree of application, and on the level of the four dimensions we find; the dimension of information technology got the highest average (3.98), then total quality standards with an average of (3.90), and third and fourth there exist the two dimensions of the organizational structures and the university operations and both of it with an average of (3.87), and all the dimensions are applied with a large degree, the results also showed that there are no statistically significant differences; at the level of (α ≤.05) between the respondents' answers about the reality of business process reengineering in the two universities due to the variables (gender, age, educational qualification, job title, place of work, years of experience). Based on the results, the researcher presented a set of recommendations and suggestions; the need for optimal employment of information technology, and keeping abreast of all that is new in the approach of business process reengineering, and benefit from the successful experiences in it, provided that what mentioned before is among the first priorities of the university, and establishing an independent department to continuously reengineer business processes, and remove any obstacle that may face the application of the business process reengineering approach, the researcher also suggests conducting future studies related to identifying the impact of the use of computerized artificial intelligence on the effectiveness of business process reengineering in private Palestinian universities, in addition to trying to build a proposed model for developing the management of the public university in Palestine in light of the approach of business process reengineering.
Keywords: Business process re-engineering; Human resources performance; Palestine private university; Gaza private university